Studi Fenomenologi Pengalaman Ibadah Pasien Islam yang di Rawat dengan Pendekatan Spiritual Islam di Rumah Sakit Aisyiah Bojonegoro dan Rumah Sakit Haji Surabaya - Abu Bakar; Ninuk Dian Kurniawati (Universitas Airlangga, 2019)
Background : Nursing theory of caring in the context of Islamic culture can be interpreted as the nurse facilitates the patient's worship and in turn, the nurse received a reward from God for this action (Lovering, 2008). Islamic nursing still not fully implemented inIslamic hospitals. This study aimed to understand the Islamic patients’ worship experience.Method : The method used in this study was phenomenological study. Sample consisted 5 patients and 6 nurses who met inclusion criteria, recruited bypurposive sampling. This study was conducted at Haji General Hospital Surabaya and AisyiahIslamic Hospital Bojonegoroduring August to December 2013. Data were collected by interviewing respondents and analyzed using the seven step of qualitative data analysis by Collaizi.Result : The results showed that not all respondents conductIslamic worship during hospitalization, particularly the obligation performing prayers five times a day. This is due to physical weaknesses, and feel of uncleanliness. These conditionswere also weakened by the lack of spiritual nursing care by nurses. Nurses had provide patients with prayer time reminder, prayer kit,Qibla direction,wudoo kit, but nurses did not conduct Islamic caring assessment and nursing diagnosis. Moreover, spiritual nursing process was not documented because of the high workload.Discussion : Further discussion about Islamic nursing care and how it is fulfilled is needed. This can be about the best way to introduce worship to Moslem patients and how to perform it during illness. Nurses should also conduct a proper assessment about the patient’s spiritual needs and implementation of worshipand how they want these needs to be helped be nurses.